Development of microsatellite markers for differentiation of Gracilaria species / Song Sze Looi - Song, Sze Looi (2013)

(untitled)
Gracilaria is a red seaweed that has been cultivated worldwide and is commercially used for food, fertilizers, animal fodder and hydrocolloids. However, the high morphological plasticity and the lack of distinctive reproductive structures often lead to the misidentification in the traditional identification of Gracilaria species. Molecular markers are important especially in the correct identification of Gracilaria species with high economic value. Various types of molecular markers, for example random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP) have been used in the study of seaweeds but there are always limitations arising from each technique. Microsatellite markers or simple sequence repeats (SSRs), are the markers of choice as they have shown to be more polymorphic, relatively abundant, of multiallelic nature and co-dominant inheritance in the molecular study of plants. The objective of this research is to mine the microsatellite markers from chloroplast genome and expressed sequence tag (EST) database of Gracilaria species deposited at the GenBank using available bioinformatics tools. The genomic SSR markers and EST-SSR markers obtained were then be used to assess their suitability for differentiating between different populations and species of Gracilaria. We also compared the variability of cox1 gene marker with the microsatellite marker that we developed and examined the polymorphism, number and pattern of SSRs from both genomic and ESTs of Gracilaria tenuistipitata. Most of the Gracilaria specimens were collected at various localities in Malaysia and some of the specimens were provided by the collaborators from other countries. For the analysis on G. tenuistipitata, eight SSRs were obtained from the chloroplast genome of G. tenuistipitata. Two primer-pairs (GT5 and GT8) showed iii polymorphisms on the specimens tested and the combinations of these two primer-pairs were able to differentiate G. tenuistipitata from the west coast of Peninsular Malaysia from populations facing the South China Sea. In addition, ten SSRs were obtained from the ESTs of G. tenuistipitata and the combined dataset of two primer-pairs (GT12 and GT18) generated four genotypes on the specimens tested and the populations from Kuah (Malaysia) and Pattani (Thailand) were grouped into two distinct clades. For the analysis on Gracilaria species, one (primer-pair P3) out of 33 primerpairs developed from the ESTs of Gracilaria species was able to distinguish between three different Gracilaria species, namely G. changii, G. fisheri and G. manilaensis which are morphologically indistinguishable. This marker can also differentiate the same species of Gracilaria from different populations, for example G. changii from Morib, Selangor has its unique allele that can be distinguished from other populations. Comparison of two different molecular markers, primer-pair P3 and cox1 gene showed that cox1 gene is more variable than the microsatellite marker that we developed. Six haplotypes (C1 – C6) were obtained using cox1 gene while only three genotypes (M1 – M3) were obtained using primer-pair P3. Our study also showed that the number and polymorphism of SSR markers obtained from ESTs were higher than the genomic SSR markers but more different kind of motifs (mono-, di-, and trinucleotide) were observed in genomic SSR markers. Development of molecular markers, particularly the microsatellite markers in distinguishing different populations and across related species, is essential to select valuable strains of the species for cultivation. Further studies in developing microsatellite markers from seaweeds with high economic value such as Gracilaria sp. will be most beneficial to the seaweed industry.